Panduan Pelayanan Bedah Digestif Selama Masa Pandemi COVID-19: Perhimpunan Dokter Spesialis Bedah Digestif Indonesia (IKABDI) - Nugroho, Adianto; Arifin, Fransicus; Widianto, Perwira; Wibowo, Agung Ari; Handaya, A. Yuda; Kristian, Iwan; Rivai, M Iqbal; Mulyawan, Made; Niam, Mohammad; Budiono, Parish; Putro, Mamiek Dwi; Warsinggih, Warsinggih (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Digestive surgery service including surgical management of gastrointestinal disease and digestive cancers are experiencing the impact of COVID-19 pandemic. Therefore it is necessary to formulate recommendation for digestives surgery service, as guidelines to engage in case-by-case assessment of particular patients with digestive diseases. We are aware that the knowledge and science of COVID-19 are still evolving, with new progression every day. This recommendation reflect actual condition and are subject for future adjustment in the future.